Molecular aspects and comparative genomics of bacteriophage endolysins - Oliveira, Hugo Alexandre Mendes (2013)
Phages are recognized as the most abundant and diverse entities on the planet. Their diversity is predominantly determined by their dynamic adaptation capacities, when confronted with different selective pressures in an endless cycle of co-evolution with a widespread group of bacterial hosts. At the end of the infection cycle, progeny virions are confronted with a rigid cell wall that hinders their release into the environment and the opportunity to start a new infection cycle. Consequently, phages encode hydrolytic enzymes, called endolysins, to digest the peptidoglycan. In this work, we bring to light all phage endolysins found in completely sequenced double stranded nucleic acid phage genomes and uncover clues that explain the phage-endolysin-host ecology that led phages to recruit unique and specialized endolysins.